New directions in the psychology of optimal performance in sport: flow and clutch states. (August 2017) - Swann, Christian; Crust, Lee; Vella, Stewart A.
Highlights: Flow is the primary framework for studying optimal functioning in sport. Emerging evidence proposes a more dynamic perspective including a second state. We review recent advances and examine both flow and clutch states. We also examine relationships between 'open' and 'fixed' goals and each state. Questions around conceptualisation, measurement, and application are discussed. Abstract : Csikszentmihalyi's conceptualisation of flow is the primary framework for understanding the psychology of optimal experience and performance in sport. However, emerging evidence suggests a more dynamic, multi-state perspective. This review focuses primarily on recent studies highlighting a second, overlapping 'clutch' state which – in addition to flow – underlies optimal performance in sport. We also examine how the nature of goals ('open' or 'fixed') athletes pursue influence the experience of flow and clutch respectively. This new, integrated model of psychological states underlying optimal performance raises questions around conceptualisation and methodology employed in the field to date. These implications are outlined, and recommendations are provided for more critical and accurate measurement of both flow and clutch as overlapping, yet distinct, states.